(untitled) (Stato, Chiese e pluralismo confessionale, 2009)
his article is a lecture part of the Political Theory Ph.D. course (Director: Full Professor Sebastiano Maffettone), held at the LUISS “Guido Carli” University (Rome) on 13 March 2009. It is due to be published in Quaderni del dottorato, Torino, Giappichelli, 2009. SOMMARIO: 1. Introduction – 2. Part I: Theological and Historical Roots of Western Constitutionalism – 2.1. King-Servant of God vs. Tyrant-Servant of the Devil – 2.2. Hobbes and la religion de l’État – 2.3. John Locke’s Principle of Tolerance. The Modern Constitutionalism – 2.4. Roger Williams: The Apostle of Religious Liberty. The Roots of American Secularism – 3. Part II: The secularismlaïcité – 3.1. The Double Separation (Emancipation): State from Religion, Religion from the State – 3.2. Islam and la laïcité à la française – 3.3. Individual Rights vs Group Rights – 4. Conclusion. Secularism and Supranational Constitutionalism